Determination of Palladium and Gold in Water and Geological Samples by FAAS after Preconcentration - Chang Han, De; Zhang, Dong (Asian Journal of Chemistry, 2015)
A new preconcentration and separation flame atomic absorption spectrophotometry (FAAS) method was developed for the determination of trace of palladium and gold ions in water and geological samples. The method was based on sorption of noble metal ions on the porous nano-barium strontium titanate by reversed-phase suspension polymerization (PBST-RSP) and sol-gel method. The possible parameters influencing the enrichment were optimized. In pH range of 6-7, Pd(II) and Au(III) could be quantitatively retained by PBST-RSP. The analytes retained on PBST-RSP were effectively eluted with 0.1 moL/L HNO3 solution. At optimum conditions, the method detection limits (3s) of 0.012 μg/L for Pd and 0.019 μg/L for Au along with enrichment factors of 100 were obtained. Finally, established method has been successfully applied for the determination of Pd and Au in water and geological samples with satisfactory results.